Anisotropy studies around the galactic centre at EeV energies with the Auger Observatory - Abraham, J; Aglietta, M; Aguirre, C; Allard, D; Allekotte, I; Allison, P; Alvarez, C; Alvarez-Muñiz, J; Ambrosio, M; Anchordoqui, L; Anjos, J; Aramo, C; et al. (2007)
Data from the Pierre Auger Observatory are analyzed to search for anisotropies near the direction of the Galactic Centre at EeV energies. The exposure of the surface array in this part of the sky is already significantly larger than that of the fore-runner experiments. Our results do not support previous findings of localized excesses in the AGASA and SUGAR data. We set an upper bound on a point-like flux of cosmic rays arriving from the Galactic Centre which excludes several scenarios predicting sources of EeV neutrons from Sagittarius A. Also the events detected simultaneously by the surface and fluorescence detectors (the 'hybrid' data set), which have better pointing accuracy but are less numerous than those of the surface array alone, do not show any significant localized excess from this direction. © 2006 Elsevier B.V. All rights reserved.